2019
DOI: 10.1093/cdn/nzz039.p18-018-19
|View full text |Cite
|
Sign up to set email alerts
|

Population Impact of Adhering to the Mediterranean Diet and Physical Activity on All-cause Mortality: The Seguimiento Universidad De Navarra (SUN) Cohort (P18-018-19)

Abstract: Objectives We assessed the population impact of the joint effect of the Mediterranean Diet (MedDiet) and physical activity (PA) in a Spanish cohort. Methods We used data from the SUN (“Seguimiento Universidad de Navarra) study, a dynamic cohort of university graduates. We used a MedDiet score (MDS) of 0–9 points and PA score of 0–8 points. Adjusted multivariable Cox regression models were used to study the individual and join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Two large studies, in which members of our group collaborated, demonstrated the efficacy of the Mediterranean diet (MD) in preventing cardiovascular diseases and reducing mortality. Thus, the "Seguimiento Universidad de Navarra" (University of Navarra Follow-up) (SUN study), in a cohort of 20,127 participants, found that poor adherence to the Mediterranean diet and low physical activity levels accounted for almost 30% of all-cause mortality [9]. Another multicentre study, the "Prevencion con Dieta Mediterránea" (PREDIMED study), which included 7447 participants at high cardiovascular risk followed up for 5 years, demonstrated that the incidence of major cardiovascular events was lower among those assigned to a Mediterranean diet supplemented with extra-virgin olive oil or nuts than among those assigned to a reduced-fat diet [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two large studies, in which members of our group collaborated, demonstrated the efficacy of the Mediterranean diet (MD) in preventing cardiovascular diseases and reducing mortality. Thus, the "Seguimiento Universidad de Navarra" (University of Navarra Follow-up) (SUN study), in a cohort of 20,127 participants, found that poor adherence to the Mediterranean diet and low physical activity levels accounted for almost 30% of all-cause mortality [9]. Another multicentre study, the "Prevencion con Dieta Mediterránea" (PREDIMED study), which included 7447 participants at high cardiovascular risk followed up for 5 years, demonstrated that the incidence of major cardiovascular events was lower among those assigned to a Mediterranean diet supplemented with extra-virgin olive oil or nuts than among those assigned to a reduced-fat diet [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two large studies, in which members of our group collaborated, demonstrated the e cacy of the Mediterranean diet (MD) in preventing cardiovascular diseases and reducing mortality. Thus, the "Seguimiento Universidad de Navarra" (University of Navarra Follow-up) (SUN study), in a cohort of 20 127 participants, found that a poor adherence to the Mediterranean diet and low physical activity levels account for almost 30% of all-cause mortality 9 . In other multicentre study, the "Prevencion con Dieta Mediterránea" (PREDIMED study) that included 7447 participant at high cardiovascular risk with a 5 years of follow-up, demonstrated that the incidence of major cardiovascular events was lower among those assigned to a Mediterranean diet supplemented with extra-virgin olive oil or nuts than among those assigned to a reduced-fat diet 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Dos grandes estudios han demostrado el papel de la dieta mediterránea (DiMed) como factor de riesgo modificable en la prevención de enfermedades cardiovasculares, así como reduciendo la mortalidad. En el estudio Seguimiento Universidad de Navarra (SUN) se observó que una adherencia pobre a la DiMed junto con la realización de poco ejercicio físico, representaba el 30% de todas las causas de mortalidad dentro de su cohorte de 20.127 participantes [159].…”
unclassified